Parenchymal liver blood volume and dynamic volume perfusion CT measurements of hepatocellular carcinoma in patients undergoing transarterial chemoembolization - Rathmann, Nils-Andreas; Budjan, Johannes; Henzler, Thomas; Smakic, Arman; Schönberg, Stefan; Diehl, Steffen J. (Anticancer research, 2017)
Aim: Prospective comparison of cone beam C-Arm CT based parenchymal liver blood volume (PLBV) and dynamic volume perfusion CT (dVPCT) measurements in patients with hepatocellular carcinoma (HCC) undergoing transarterial chemoembolisation (TACE) with drug-eluting beads (DEB). Patients and Methods: In 16 patients, changes of PLBV and dVPCT measurements [arterial liver parenchyma (ALP); temporal maximum intensity projection (MIP); hepatic perfusion index (HPI); portal venous parenchyma] were correlated to one another and to the modified Response Evaluation Criteria in Solid Tumors (mRECIST). Results: After TACE, the following parameters showed a statistically significant change (p<0.05) in mean value: PLBV: −4.85 ml/100 ml, ALP: −4.14 ml/100 ml/min, MIP: −0.23 Houndsfield units, HPI: −5.39%, and mRECIST: −20.53 mm. Pre-to-post TACE differences in PLBV showed only weak to very weak correlation to dVPCT parameters (r2<0.24). Conclusion: Although PLBV and dVPCT parameters showed only a weak to very weak correlation, both methods validly assessed changes in arterial tumor vascularity after DEB TACE.